Efficacy of Moringa oleifera Seed Husk as Adsorptive Agent for Trihalomethanes from a Water Treatment Plant in Southwestern, Nigeria - Aderonke Adetutu Okoya; Olasunkanmi Olalekan Olaiya; Abimbola Bankole Akinyele; Nnenneh Oruada Ochor (Journal of Chemistry)
Trihalomethanes (THMs) are formed when excess chlorine during chlorination of water reacts with organic material in water. They have mutagenic and carcinogenic properties. Moringa oleifera (MO) has found wide acceptance by many people in Nigeria who have used it for food for both humans and fauna, for health purposes, and as a coagulant for water treatment. However, the seed husks are currently discarded as waste and they have not been used as adsorbent to remove THMs from water. The physicochemical properties of both the treated and raw surface water were determined using standard methods, and the concentration of THMs was determined from the water treatment plant at different stages of treatment using gas chromatography with flame ionization detector (GC-FID). Recovery experiments were carried out to validate the procedure. The efficiencies of activated carbon of Moringa oleifera seed husk (MOSH) adsorbent for the removal of THMs in the water and as a coagulant for water treatment were also assessed. Batch adsorption experiments were carried out, and different parameters such as pH (5, 7, and 9), adsorbent dosage (0.2, 0.4, and 0.8 g), contact time (30, 60, and 90 minutes), and initial concentration (0.2, 0.4, and 0.6 mg/l) were optimized for the removal of trichloromethane and tribromomethane using the MOSH activated carbon. Experimental adsorption data from different initial concentrations of trichloromethane and tribromomethane were used to test conformity with Langmuir and Freundlich adsorption isotherms. The percentage recovery from our procedures ranged from 96.0 ± 1.41 to 100.0 ± 0.00 for trichloromethane while for tribromomethane the range was 60 ± 2.82 to 100.0 ± 0.00. The mean percentage adsorption efficiencies for the simulation experiment ranged from 34.365 ± 1.41 to 93.135 ± 0.57 and from 41.870 ± 0.27 to 94.655 ± 0.41 for trichloromethane and tribromomethane, respectively. The optimum conditions for both trichloromethane and tribromomethane were pH 9, 0.8 g adsorbent dosage, 60-minute contact time, and 0.6 mg/l initial concentration. The optimum values of these parameters used for the adsorption of the two THMs in the surface water serving the treatment plant gave an efficiency of 100.00 ± 0.00%. The turbidity values for the coagulation experiment reduced from 9.76 ± 0.03 NTU in the raw water before coagulation to 5.92 ± 0.13 NTU after coagulation while all other physicochemical parameters of the surface water decreased in value except conductivity and total dissolved solid which increased from 104.5 ± 3.54 to 108.0 ± 2.83 μS/cm and 63.00 ± 11.31 to 83.0 ± 8.49 mg/l, respectively. The experimental data best fit into Langmuir than Freundlich adsorption isotherm. The study concluded that MOSH activated carbon could serve as an adsorbent for the removal of THMs, calcium, and sulphur from water samples.